2015
DOI: 10.7235/hort.2015.15052
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Growth Bioregulators Influences Floral Traits, Corm- associated Traits and Chemical Constituents in Gladiolus grandiflorus L.

Abstract: Gladiolus is one of the most popular cut flowers in the world floral market and is highly attractive to consumers. The production of poor-quality gladiolus spikes is one of the most important hurdles to obtaining high prices for this crop. The main objectives of this study were to improve the quantitative characteristics of gladiolus spikes, to increase propagule production and to enhance chemical constituent levels in leaves to help improve plant growth. We performed foliar application of bioregulators, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
3
2
0
Order By: Relevance
“…In line with previous studies on syngonium (Abd El-Aziz et al 2007), gladiolus (Hashish et al 2015;Sajjad et al 2015) and tomato (Farouk et al 2012), Th application increased the nutrient contents in coriander and fenugreek. In a study on sunflower, the contents of toxic ions Na + , Ca2 + and Clwere significantly lower, while cytoplasmic K + content, which is essential for survival in stress condition, were higher in Th-treated plants (Sayed & Gadallah 2002).…”
Section: ____________________________________________________________supporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous studies on syngonium (Abd El-Aziz et al 2007), gladiolus (Hashish et al 2015;Sajjad et al 2015) and tomato (Farouk et al 2012), Th application increased the nutrient contents in coriander and fenugreek. In a study on sunflower, the contents of toxic ions Na + , Ca2 + and Clwere significantly lower, while cytoplasmic K + content, which is essential for survival in stress condition, were higher in Th-treated plants (Sayed & Gadallah 2002).…”
Section: ____________________________________________________________supporting
confidence: 91%
“…Reda et al (2005) demonstrated that the application of Th at 60 ppm resulted in higher content of total phenolics in thyme. Similar results were obtained on gladiolus, where phenolics increased in response to Th foliar application (Sajjad et al 2015). Results of El-Bassiouny and Sadak (2015) in Linum usitatissimum also revealed that vitamins, ascorbic acid and α-tocopherol induced considerable reduction in lipid peroxidation but an increase in superoxide dismutase as an antioxidant.…”
Section: ____________________________________________________________supporting
confidence: 74%
See 1 more Smart Citation
“…Increase in floret weight spike -1 with GA 3 was attributed to the production of more number of bigger size florets as gibberellins are important for differentiation and growth of more number of flower primordia (Alpi et al, 1976). These results are in line with the findings of Sajjad et al, (2015) in gladiolus.…”
Section: Floret Weight Spike -1 (G)supporting
confidence: 81%
“…One such compound is 1-naphthaleneacetic acid (NAA), which is a synthetic auxin that plays multiple roles in regulating vegetative and reproductive growth. It is considered safe for plants at recommended concentrations and has been used in tissue culture and fruit thinning (Sajjad et al, 2015;Yoo et al, 2016;Tepkaew et al, 2022). As a growth regulator, NAA affects plant reproduction, including panicle development (Jain and Khurana, 2009).…”
Section: Introductionmentioning
confidence: 99%